ANALISIS PENYAJIAN PENDAPATAN DALAM LAPORAN LABA RUGI PADA PT UNILEVER INDONESIA Tbk - Eufemia Nunu; Sandra Dwi Rapianti; Mutiara Yulisma; Naysilla Ayu Pradista; Sun Rumondang (Jurnal Riset Multidisiplin Edukasi, 2026)
Revenue is one of the important elements in financial statements used to measure a company's success in carrying out its operational activities. Proper presentation of revenue in the income statement provides accurate information that can be used as a basis for decision-making by management, investors, and other external parties. This study aims to analyze the presentation of revenue in the income statement of PT Unilever Indonesia Tbk and examine the company's revenue development over a certain period. The research method used is a descriptive method with a qualitative approach through the analysis of the company's financial statements obtained from secondary data sources. The results indicate that the presentation of revenue at PT Unilever Indonesia Tbk has been prepared in accordance with applicable financial accounting standards, providing a clear overview of the company's financial condition. In addition, the company's revenue development has experienced fluctuations influenced by various factors such as market conditions, consumer demand, business competition, and economic conditions.